Bioluminescence properties of Thelepus japonicus (Annelida: Terebelliformia). (13th May 2019) - Kin, Ikuhiko; Jimi, Naoto; Oba, Yuichi
Abstract: Terebelliformia is a benthic group of marine annelid worms. The bioluminescence of several species has been reported in taxonomical and histological literature, but very little information is known about the biochemical aspects of this phenomenon. In this study, we examined the basic properties of the luminescence system using an extract of the Japanese terebelliform worm, Thelepus japonicus . The bioluminescence extract was soluble in water, and emitted blue‐green light at λmax 508 nm following the addition of divalent cations. This triggering action was highly specific to Fe 2+ and addition of ATP, H2 O2 or coelenterazine did not enhance activity. The bioluminescence was inactivated by heat treatment and organic solvents, indicating the involvement of a protein component. These results suggested that Thelepus worm produces light using a novel system that differs from that in other known luminescent annelids.